1994
DOI: 10.1002/recl.19941130303
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐induced decomposition of coenzyme B12 and variants

Abstract: The acid‐catalyzed heterolytic cleavage of the Co‐C bond in coenzyme B12 (1) and adocobinamide hydroxide (2) was studied using the excess‐acidity functions of Cox and Yates. The results are compared to the acid‐induced decomposition of methyl(5′‐deoxyribofuranosyl)cobalamin (3) and (2‐ethoxyethyl)cobalamin (4). Evidence is presented to view the bond cleavage in the compounds 1, 2 and 3 as an A2 mechanism or as an Ia substitution at Co3+, with water as the nucleophile, and in 4 as an A1 mechanism. For 1, the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…The published stable pH range for all analyzed cobalamins is pH 4–7, with lower pHs resulting in lower retention on a C18 SPE and acid‐induced heterolysis of Ado‐Cbl . Me‐Cbl and Ado‐Cbl are particularly labile, so we focused on decreasing processing time (from 66 to 8 h for the preconcentration step) and eliminating the 2 nd SPE (pH 2) step required in previously published methods .…”
Section: Results and Discusionmentioning
confidence: 99%
“…The published stable pH range for all analyzed cobalamins is pH 4–7, with lower pHs resulting in lower retention on a C18 SPE and acid‐induced heterolysis of Ado‐Cbl . Me‐Cbl and Ado‐Cbl are particularly labile, so we focused on decreasing processing time (from 66 to 8 h for the preconcentration step) and eliminating the 2 nd SPE (pH 2) step required in previously published methods .…”
Section: Results and Discusionmentioning
confidence: 99%
“…3,34 As is the case for all organocobalt compounds with b oxygen substituents, 3 AdoCbl is acid labile, and undergoes a heterolytic process which yields aquacobalamin (H 2 OCbl + ), adenine, and 2,3-dihydroxy-4-pentenal, in a process that is both specific acid-catalyzed and general acid (solvent) catalyzed. 3,34,75, 76 The competing process is carbon-cobalt bond homolysis, which is known to proceed through a solvent-caged cob(II)alamin-Ado • radical pair and consequently to be diffusion controlled in solution. 34,51,77,78, 79 The fate of the caged radical pair varies with conditions.…”
Section: Non-enzymatic Thermolysis Of Ado(im)cblmentioning
confidence: 99%
“…A striking feature of the organometallic chemistry of coenzyme B 12 is the minimization of nonproductive side reactions, for example β-hydride or β-alkoxide eliminations that would cleave the Co−C bond irreversibly (Scheme ). The latter pathway was observed in early studies aimed at elucidation of the structure of Ado-B 12 , which indicated that cyanide was replaced on vitamin B 12 by a nucleoside that released 1 equiv.…”
Section: Introductionmentioning
confidence: 99%